Modulation of visual attention by prismatic adaptation - Clarke, Stephanie; Crottaz-Herbette, Sonia (Neuropsychologia, 2016)
Visuo-motor adaptation via rightward-deviating prisms has been repeatedly shown to alleviate lateralized deficits in neglect, including detection of targets as well as endogenous and exogenous orienting of attention. We review here evidence relevant to the underlying neural mechanisms. Rightward prismatic adaptation was shown to shift visual field representation from right to left inferior parietal lobule, changing thus hemispheric dominance within the ventral attentional system. This change is likely to redirect visual input to the dorsal attentional system and to re-install balance between its left- and right-hemispheric components in neglect. We propose a model based on the shift in hemispheric dominance within the ventral attentional system (SHD-VAS), which offers a parsimonious explanation for the effect of rightward prismatic adaptation on spatial bias in neglect and on behavioral data in normal subjects. •Rightward prismatic adaptation induces leftward shift of sensory-motor coordinates.•R-PA shifts visual field representation from right to left inferior parietal lobule.•In neglect R-PA reduces spatial bias, but not in all tasks; few effects in normal.•Shift in hemispheric dominance in ventral attentional system: valid model for R-PA.•It accounts for effects of R-PA and predicts interactions with attentional systems.